2019
DOI: 10.3390/medicina55090606
|View full text |Cite
|
Sign up to set email alerts
|

Lung Cryobiopsy for the Diagnosis of Interstitial Lung Diseases: A Series Contribution to a Debated Procedure

Abstract: Introduction: Transbronchial cryobiopsy is an alternative to surgical biopsy for the diagnosis of fibrosing interstitial lung diseases, although the role of this relatively new method is rather controversial. Aim of this study is to evaluate the diagnostic performance and the safety of transbronchial cryobiopsy in patients with fibrosing interstitial lung disease. Materials and methods: The population in this study included patients with interstitial lung diseases who underwent cryobiopsy from May 2015 to May … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
11
0

Year Published

2020
2020
2022
2022

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 48 publications
1
11
0
Order By: Relevance
“…Peripheral HRCT fibrosis score was positively correlated with the risk of pneumothorax. Harari found that the incidence of pneumothorax was 10.9% in their study 18 . In our review, no pneumothorax occurred intraoperatively, and no pneumothorax or death occurred during the 30‐day follow‐up.…”
Section: Discussionsupporting
confidence: 45%
See 2 more Smart Citations
“…Peripheral HRCT fibrosis score was positively correlated with the risk of pneumothorax. Harari found that the incidence of pneumothorax was 10.9% in their study 18 . In our review, no pneumothorax occurred intraoperatively, and no pneumothorax or death occurred during the 30‐day follow‐up.…”
Section: Discussionsupporting
confidence: 45%
“…With definite or high diagnostic confidence, the concordant diagnoses were as high as 95% for TBLC at MDD 11 . Harari et al indicated that the proportion of diagnoses between TBLC and SLB was 88% and 90%, respectively 18 . Compared with SLB, the relatively small biopsy tissue is the main limitation of TBLC in ILDs pathological diagnosis.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Transbronchial lung cryobiopsy (TBLC) can yield significantly larger biopsies than TBLB [5,6] and has been suggested as an acceptable alternative to SLB in achieving a diagnosis of ILD due to its high diagnostic yield, adequate representation of the pattern of lung injury, and an acceptable safety profile. Though reports are variable and largely retrospective in nature, the diagnostic yield of cryobiopsy has been reported between 70 and 80% [7][8][9][10][11][12]. However, 2 recently published randomized trials investigating the concordance of TBLC and SLB, by performing them concurrently on the same patient, have reached different conclusions.…”
Section: Introductionmentioning
confidence: 99%
“…In a recent retrospective study by Harari et al, 52 the diagnostic performance and safety of cryobiopsy was assessed in a cohort of 73 patients, among which, a specific diagnosis was reached in 64 cases (sensitivity: 88%). Of the remaining 9 cases, 5 (7%) were inadequate and 4 (5%) were found to be nondiagnostic.…”
Section: Diagnostic Yield In Ildmentioning
confidence: 99%